2020
DOI: 10.1155/2020/3154619
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation Analysis of Journal Impact Factor Dynamics Based on Submission and Citation Rules

Abstract: The variation of the journal impact factor is affected by many statistical and sociological factors such as the size of citation window and subject difference. In this work, we develop an impact factor dynamics model based on the parallel system, which can be used to analyze the correlation between the impact factor and certain elements. The parallel model aims to simulate the submission and citation behaviors of the papers in journals belonging to a similar subject, in a distributed manner. We perform Monte C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…• Journal impact factor and the publication time of articles are helpful to rank scientific articles [3] [5] [16] [17] [24].…”
Section: Heterogeneous Scholarly Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…• Journal impact factor and the publication time of articles are helpful to rank scientific articles [3] [5] [16] [17] [24].…”
Section: Heterogeneous Scholarly Networkmentioning
confidence: 99%
“…Scholarly impact assessment and ranking have always been a hot issue, which plays an important role in the process of the dissemination and development of academic research [1] [2] [3]. However, it is diffcult to assess the real quality of academic articles due to the dynamic change of citation networks [4].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al. (2020) modeled the IF as a function of the average review time, the average number of references, and the distribution of the citation's ages, and Zhou et al. (2019) modeled the impact of citation networks on the IF.…”
Section: Introductionmentioning
confidence: 99%
“…Through a statistical analysis, Huang et al (2019) demonstrated that modifying a journal's status to "Open Access" leads to a higher IF. Zhou et al (2020) modeled the IF as a function of the average review time, the average number of references, and the distribution of the citation's ages, and Zhou et al (2019) modeled the impact of citation networks on the IF. Hoffmann et al (2014) applied social network analysis to the assessment of scientific impact.…”
mentioning
confidence: 99%
“…Scholarly impact evaluation has always been a hot topic, which is benefcial to promote the public understanding and application of scientifc achievements [1][2][3]. Nevertheless, assessing and computing academic achievements has proven to be a difcult task due to the constantly changing nature of citation networks [4,5].…”
Section: Introductionmentioning
confidence: 99%